2014
DOI: 10.1039/c3dt53554a
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of palladium nanoparticles using Pulicaria glutinosa extract and their catalytic activity towards the Suzuki coupling reaction

Abstract: Green synthesis of nanomaterials finds the edge over chemical methods due to its environmental compatibility. Herein, we report a facile and eco-friendly method for the synthesis of palladium (Pd) nanoparticles (NPs) using an aqueous solution of Pulicaria glutinosa, a plant widely found in a large region of Saudi Arabia, as a bioreductant. The as-prepared Pd NPs were characterized using ultraviolet-visible (UV-vis) spectroscopy, powder X-ray diffraction (XRD), transmission electron microscopy (TEM), energy-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(102 citation statements)
references
References 51 publications
9
93
0
Order By: Relevance
“…Our results are consistent with those of previous studies that have reported the synthesis of PdNPs using several biological templates, including extracts of coffee and tea, leaf extracts of Anacardium occidentale, Pulicaria glutinosa, and Evolvulus alsinoides, and saponin. 8,21,[35][36][37] effects of TUB-a and PdNPs on MDa-MB-231 human breast cancer cell viability WST-8 assay was performed to investigate the cytotoxicity of TUB-A and PdNPs on human breast cancer cells. We first tested the cytotoxic effects of TUB-A and PdNPs, dose dependently.…”
Section: Results and Discussion Synthesis And Characterization Of Pdnpsmentioning
confidence: 99%
“…Our results are consistent with those of previous studies that have reported the synthesis of PdNPs using several biological templates, including extracts of coffee and tea, leaf extracts of Anacardium occidentale, Pulicaria glutinosa, and Evolvulus alsinoides, and saponin. 8,21,[35][36][37] effects of TUB-a and PdNPs on MDa-MB-231 human breast cancer cell viability WST-8 assay was performed to investigate the cytotoxicity of TUB-A and PdNPs on human breast cancer cells. We first tested the cytotoxic effects of TUB-A and PdNPs, dose dependently.…”
Section: Results and Discussion Synthesis And Characterization Of Pdnpsmentioning
confidence: 99%
“…The details about the procedure of the collection of P. glutinosa and the preparation of extract are given in our previous study [40].…”
Section: Methodsmentioning
confidence: 99%
“…This clearly points towards the destruction of the regular layered structure of GRO and the formation of a few layer stacked HRG sheets in PG-HRG-Pd-1 after the reduction with PGE. Besides, the XRD spectrum of PG-HRG-Pd-1 also contains several reflections at 40 However, after oxidation, the sp 2 character in graphene is destroyed and various defects are formed in GRO, due to which the characteristic bands of graphene in this case are shifted to 1602 and 1340 cm −1 , respectively. Notably, these bands are relocated closer to their ideal positions after the reduction with PGE in the Raman spectrum of PG-HRG-Pd-1, i.e., the G band is shifted from 1602 to 1592 cm −1 , whereas the D band is relocated from 1340 to 1336 cm −1 .…”
Section: Xrd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the plant and preparation of the PE are given elsewhere. 38 The PE solution, employed for the reduction of GRO, was made using 0.1 g of PE dissolved in 1 mL of solvent.…”
Section: Introductionmentioning
confidence: 99%